Atrioventricular Valve Regurgitation in Single Ventricle Heart Disease: A Common Problem Associated With Progressive Deterioration and Mortality. Issue 11 (2nd June 2020) - Tseng, Stephanie Y.; Siddiqui, Saira; Di Maria, Michael V.; Hill, Garick D.; Lubert, Adam M.; Kutty, Shelby; Opotowsky, Alexander R.; Possner, Mathias; Morales, David L. S.; Quintessenza, James A.; Alsaied, Tarek
Abstract: The Fontan procedure has provided patients with single ventricle physiology extended survival into adulthood and in many cases has improved their quality of life. Atrioventricular valve regurgitation (AVVR) is common in single ventricle patients and is associated with increased risk of mortality. AVVR is more common in patients with a systemic tricuspid or common atrioventricular valve but is generally progressive irrespective of underlying valve morphology. AVVR can be attributable to diverse structural and functional abnormalities at multiple levels of the valvar apparatus, as well as ventricular dysfunction and dilation. Multiple imaging modalities including recent advances in 3‐dimensional echocardiography and cross‐sectional imaging have been used to further understand AVVR. Surgery to address AVVR must be tailored to the underlying mechanism and the timing of surgical repair should be chosen carefully. In this review, we discuss the etiologies, treatment options, surgical timing, and outcomes of valve repair or replacement for AVVR in patients with single ventricle congenital heart disease, with a focus on those with a Fontan circulation as AVVR is associated with increased risk for Fontan failure and mortality. In‐depth understanding of the current literature will help guide clinicians in their approach and management of AVVR in this population.